Development of Liposome containing sodium deoxycholate to enhance oral bioavailability of itraconazole - Zhenbao Li; Meiyu Zhang; Chang Liu; Shiwei Zhou; Wenjuan Zhang; Tianyang Wang; Mei Zhou; Xiaohong Liu; Yongjun Wang; Yinghua Sun; Jin Sun (Elsevier, 2017)
The aim of this study was to enhance oral bioavailability of itraconazole (ITZ) by developing Liposome containing sodium deoxycholate (ITZ-Lip-NaDC). The liposome, consisting of egg yolk lecithin and sodium deoxycholate, was prepared by thin-film dispersion method. Differential Scanning Calorimetry (DSC) results indicated an amorphous state in the liposome. The physicochemical characteristics including particle size, morphology, entrapment efficiency, dissolution properties were also investigated. The performance of single-pass intestinal infusion exhibited that the transport order of intestinal segment was jejunum, duodenum, colon and ileum, and that all the segments participated in the absorption of ITZ in intestinal tract. The bioavailability study in rats showed that the AUC0-72 of the liposome was nearly 1.67-fold higher than that of commercial capsules (SPORANOX) in terms of oral administration, and the RSD of AUC0-72 of ITZ-Lip-NaDC was also decreased. Our results indicated that ITZ-Lip-NaDC liposome was facilitated to improve dissolution efficiency, augment transmembrane absorption, and then enhance the oral bioavailability of ITZ, successfully.